Albania in the EU? Constitutional Implications of the Doctrine of Supremacy of EU Law - Gjevori, Anduena (Richtmann Publishing, 2012)
The doctrine of the supremacy of Community Law as developed by the ECJ has been at the heart of juridical and doctrinaldebates. One of the most acute issues for national courts in the European Union has been whether to accept EU law as the supreme lawof the land, giving it primacy even when conflicting with national constitutional provisions. The judicial approach regarding this principleeven in the new Member States from Central Eastern Europe has been varying. Therefore, we analyze the position of a potentialMember State such as Albania, the role of its Constitution and Constitutional Court, regarding the doctrine of supremacy of EU law asdeveloped by the ECJ. Many Albanian authors, according to the Kelsenian concept of the legal system as a pyramid, interpret Article116 of the Albanian Constitution as creating a hierarchy between the sources of the law, by placing the Constitution in the first place.However, the Albanian Constitution was drafted to facilitate the Euro-Atlantic integration of the country and includes specific articles forthe abovementioned integration. One of them - Article 122/3 relevant to the doctrine of supremacy of EU law - will be analysed tounderstand whether its language upholds the doctrine of supremacy of EU law. We will supplement such analysis with a general view ofthe constitutional provisions and Constitutional Court decisions, which address the problems of international law in the Albanian legalsystem. Such analysis is both important and timely since the pending ‘candidate status’ for Albania will both widen and deepen Albania’srelationship with the EU making the issue of the supremacy of EU law legally more pressing and socially and politically more pertinent.